If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(u-2)=7u+4-2(-2u-2)
We move all terms to the left:
3(u-2)-(7u+4-2(-2u-2))=0
We multiply parentheses
3u-(7u+4-2(-2u-2))-6=0
We calculate terms in parentheses: -(7u+4-2(-2u-2)), so:We get rid of parentheses
7u+4-2(-2u-2)
determiningTheFunctionDomain 7u-2(-2u-2)+4
We multiply parentheses
7u+4u+4+4
We add all the numbers together, and all the variables
11u+8
Back to the equation:
-(11u+8)
3u-11u-8-6=0
We add all the numbers together, and all the variables
-8u-14=0
We move all terms containing u to the left, all other terms to the right
-8u=14
u=14/-8
u=-1+3/4
| 1.7x+8-1.62x0.4x-0.32=8 | | 5p·-5=150 | | 5x+7+x+6=10 | | 4y-4+2(3y+5)=-2(y+1) | | (3x-4)^2=-25 | | 8x-(5x+5=1 | | x+(x/4)=40 | | 6x+-8=6x+2 | | –0.4(3x+8)=–3x–3.2 | | k-18=23 | | x2+4x+437=0 | | (8x-7)+(2x+4)=127 | | -14w^2+20w-3=0 | | 2775.50=2600.00(1+0.75r) | | 42+4y=-13 | | 12(x-4)+7=25 | | 25+j=-14 | | 25+j=-11 | | 1314=730(1+0.16t) | | 2x+(x-6)=458 | | 2x+6+x+7=11 | | 2x+9=3x−17 | | 18c+3=2c+5 | | 4=75+x | | -4(x+2{x-4(3x-2)})=116(5x+8) | | 120+x+130=180 | | 5x+90=15 | | 0,96x*12,5=24 | | 40=14-2x | | 123=2x-7 | | -12y-5y=3 | | 0,96x*2,4=24 |